Monitoring of body composition of volleyball athletes with anthropometry, Dexa and bod pod a comparative study - García Dávila, Myriam Zaraí; López García, Ricardo; Hernández Cruz, Germán; Rangel Colmenero, Blanca Rocío; Ramírez López, Erik (2014)
The main objetive of volleyball coaches and sports nutritionits is to monitor corporal body athletes before